Tricuspid annular plane systolic excursion as a marker of right ventricular dysfunction in pediatric patients with dilated cardiomyopathy. Issue 1 (9th December 2016) - McLaughlin, Ericka S.; Travers, Curtis; Border, William L.; Deshpande, Shriprasad; Sachdeva, Ritu
Abstract : Background: Right ventricular systolic dysfunction (RVSD) is a predictor of outcomes in dilated cardiomyopathy (DCM) in adults, but little is known in children. Tricuspid annular plane systolic excursion (TAPSE) has emerged as a reliable tool to assess RVSD. We sought to determine the prevalence and prognostic significance of RVSD using TAPSE in children with DCM. Methods: The first echocardiogram at the time of diagnosis with DCM was analyzed to obtain left ventricular ejection fraction (LVEF) and 2D TAPSE. RVSD was defined as TAPSE age‐based z‐score ≤−2. The association of a composite primary endpoint including death, mechanical support, or transplantation with RVSD was analyzed using LVEF and TAPSE. Results: Of the 96 patients, RVSD was noted in 84 (88%). During a median follow‐up of 17.5 months (IQR 1.4, 76.2), the primary endpoints were reached in 59%. There was a lower LVEF in patients with RVSD ( P =.016). Moderate or severe RVSD showed a significant association with the composite primary endpoint (unadjusted OR 2.7 [95% CI: 1.15–6.33], P =.023). Kaplan‐Meier analysis showed that the event‐free survival was significantly lower in patients with LVEF ≤30% and TAPSE z‐score ≤−4. Conclusion: Children with DCM have a high prevalence of RVSD based on reduced TAPSE, and those with moderate or severe RVSD have worse clinical outcomes.